2018 3rd Digital Heritage International Congress (DigitalHERITAGE) Held Jointly With 2018 24th International Conference on Virt 2018
DOI: 10.1109/digitalheritage.2018.8810043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating emotional engagement in digital stories for interpreting the past. The case of the Hunterian Museum’s Antonine Wall EMOTIVE experiences

Abstract: Digital storytelling has been used in cultural heritage for over two decades, yet integrating this in museum displays to encourage visitors' deep engagement, including both affective and cognitive outcomes, remains challenging and raises a number of issues. EMOTIVE is a European Union Horizon 2020 Research and Innovation project which addresses some of these as it aims to design and evaluate emotionally engaging digital visitor experiences for heritage sites and museum displays. The Hunterian, the museum of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Emotional responses to learning materials have been shown to increase motivation, attention, and facilitate effective learning (Wolfson and Case 2000;Taylor 2014;Zull and Statler 2016;Savenije and De Bruijn 2017), while heightened emotional involvement makes the learning content memorable and for longer periods of time than with emotionally neutral involvement (Ninaus et al 2019;McCrary 2002;Phelps 2004). Stories are powerful means of emotional engagement and the affective experience of learners through storytelling has been explored in online and multimedia learning environments (Mcquiggan, Robison and Lester 2008;McCrary 2002) and in heritage (Economou, Young and Sosnowska 2018;Savenije and De Bruijn 2017;Petrelli et al 2016).…”
Section: Learning Through Affective Storytellingmentioning
confidence: 99%
“…Emotional responses to learning materials have been shown to increase motivation, attention, and facilitate effective learning (Wolfson and Case 2000;Taylor 2014;Zull and Statler 2016;Savenije and De Bruijn 2017), while heightened emotional involvement makes the learning content memorable and for longer periods of time than with emotionally neutral involvement (Ninaus et al 2019;McCrary 2002;Phelps 2004). Stories are powerful means of emotional engagement and the affective experience of learners through storytelling has been explored in online and multimedia learning environments (Mcquiggan, Robison and Lester 2008;McCrary 2002) and in heritage (Economou, Young and Sosnowska 2018;Savenije and De Bruijn 2017;Petrelli et al 2016).…”
Section: Learning Through Affective Storytellingmentioning
confidence: 99%
“…The NSE has been one of the main authoring tools used in the course of the EMOTIVE project by the internal User Group of the EMOTIVE consortium and has resulted in the first prototype of the Hunterian Antonine Wall on-site experience, "The life of Ebutius", which was evaluated at the Scottish European Researchers' Night, Explorathon 2017 in the Hunterian Museum, on 29 September 2017 (Economou et al, 2019).…”
Section: The Emotive Research Projectmentioning
confidence: 99%
“…Since its first version in 2016, the NSE has been applied in a variety of contexts and used for the creation of 27 experiences in 16 museums and sites, as for example (Roussou et al, 2017), (Mirashrafi, 2017), (Katifori et al, 2019a), (Katifori et al, 2019b) and (Economou et al, 2019).…”
Section: "Real World" Appsmentioning
confidence: 99%
“…In both cases, the research demonstrated that museums housed within historic buildings can be particularly well suited to the development of new media forms. Interactive and immersive media have often been used within archaeology and museums as a means of representing the past [13][8] [28][34]. This project demonstrated that as well as being used for depiction or representation, interactive and immersive media can also be used to mediate and to guide physical, intellectual and emotional engagements with the past.…”
Section: New Creative Directions For Immersive Media and Museumsmentioning
confidence: 99%